Późnośredniowieczne naczynia z Międzyrzecza. Przyczynek do studiów nad pochodzeniem i użytkowaniem wyrobów szklanych - Sawicka, Joanna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
In the late medieval settlement layers of the gord in Międzyrzecz, a small collection of glass vessels was excavated. Several forms of tableware were reconstructed and research was conducted into the chemical composition of the glass. The examined piece of a vessel and the glass is potassium glass which comes in two varieties: calcium-potassium-magnesium-silica (CaO-K2O-MgO-SiO2) and calcium-potassium-magnesium-aluminium-silica (CaO-K2O-MgO-Al.2O3-SiO2). The forms of the vessels and the chemical composition of the examined glass indicate the basic goods manufactured in Central Europe.